DEVELOPMEMT OF LIQUIDITY REGULATION INSTRUMENTS OF REGIONAL BANK SECTOR ORGANIZATIONS - A. V. Roussavskaya (Модернизация, инновация, развитие, 2016)
Discussed in the article is a model of an improved regulatory framework for credit institutions dealing with investment projects implementation of which will make it possible for business enterprises of various economy sectors whose activities are dependent on investment resources, such as small-scale and medium-scale as well as innovation business enterprises, to reach in the coming years an entirely different level of development.